Effect of Divorce in Family Life - Adhikari, Jib Narayan (Kaladarpan कलादर्पण, 2024)
The present research is undertaken for investigating the effect of divorce in family life especially on child. For the fulfillment of the objective, the national and international articles, book and journals were reviewed. For this secondary literatures were used. Study show that divorce is always a complex matter in Nepal. Here, marriage is considered a sacred bond and divorce is considered an evil act, however, the divorce rate is increasing. The research has revealed that the circumstances of children after their parent’s divorce gets troubled, disturbed and challenged, they are subjected to mental torture, have problems with their education and childcare. It may arise due to the absence of parents. So divorce can be a major factor of concern.